Caracterização das camadas formadas pela nitretação a plasma de ferro sinterizado - Fontes, Marcos Alves (2012)
Ion nitriding is a process of thermo-physical-chemical treatment that provides a surface hardening, originated by interstitial diffusion of nitrogen on the ferrous and nonferrous alloys surfaces. Understanding and controlling the formation of the nitrided layer have considerable industrial interest due to the improvements regarding wear, corrosion and fatigue resistances on the metals and their alloys. In this work, it was performed the surface modification in sintered iron samples by ion nitriding process, with a gaseous mixture of 80% vol H2 and 20% vol N2, during times of 3 and 5 hours, using ion nitriding temperature of 500°C, 540°C and 580°C. The samples were characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses, and wear and micro-hardness tests, comparing the results with sintered and steam treatment samples. The results showed that both nitride thickness and wear resistance increased with higher nitriding time and temperature, where the temperature was the variable that most influenced the aforementioned characteristics. The XRD analysis indicated that the nitrided layer near to the surface, for all samples, consisted in a mixture of y-Fe4N and e-Fe3N phases.